2019
DOI: 10.1074/jbc.ra118.006983
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH signaling is activated in and contributes to resistance in enzalutamide-resistant prostate cancer cells

Abstract: Edited by Xiao-Fan Wang Prostate cancer is the second leading cause of cancer death among men in the United States. The androgen receptor (AR) antagonist enzalutamide is a Food and Drug Administrationapproved drug for treatment of patients with late-stage prostate cancer and is currently under clinical study for early-stage prostate cancer treatment. After a short positive response period, tumors will develop drug resistance. In this study using RNA-Seq and bioinformatics analyses, we observed that NOTCH signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Multiple molecules have participated in the progression of prostate cancer [8][9][10][11][12] . Notch signaling pathway is involved in the occurrence and development of a variety of tumors, and it can regulate a variety of cell processes, including cell differentiation, proliferation, apoptosis and migration [13,14] . When the Notch ligand specifically binds to the receptor, the Notch signaling pathway is subsequently activated, which in turn activates the transcription of the downstream gene Hes family.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple molecules have participated in the progression of prostate cancer [8][9][10][11][12] . Notch signaling pathway is involved in the occurrence and development of a variety of tumors, and it can regulate a variety of cell processes, including cell differentiation, proliferation, apoptosis and migration [13,14] . When the Notch ligand specifically binds to the receptor, the Notch signaling pathway is subsequently activated, which in turn activates the transcription of the downstream gene Hes family.…”
Section: Discussion:-mentioning
confidence: 99%
“…cancer based on clinical sample [7] . The present study aims to explore the expression and clinical significance of Notch and HIF-1α signaling pathway in the progression of prostate cancer.…”
mentioning
confidence: 99%
“…Therefore, elucidating the mechanisms of resistance to ADT is necessary. Three recent studies have shown that Notch signalling can contribute to resistance to enzalutamide (androgen receptor antagonist) [46] and that Notch inhibition combined with ADT can cause a synergistic therapeutic effect [47,48]. In addition, Notch signalling has also been implicated in docetaxel resistance [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging evidences suggest that Notch signaling pathway is one of the most important signaling pathways in drug-resistant tumor cells (32). The activated Notch signaling contributes to resistance in enzalutamide-resistant prostate cancer cells (33). Inhibition of Notch signaling reverses docetaxel resistance in prostate cancer (34).…”
Section: Discussionmentioning
confidence: 99%